2015
DOI: 10.1371/journal.pone.0145242
|View full text |Cite
|
Sign up to set email alerts
|

Light Inhibition of Shoot Regeneration Is Regulated by Endogenous Abscisic Acid Level in Calli Derived from Immature Barley Embryos

Abstract: Shoot regeneration in calli derived from immature barley embryos is regulated by light conditions during the callus-induction period. Barley cultivars Kanto Nijo-5 (KN5) and K-3 (K3) showed lower efficiency of shoot regeneration in a 16-h photoperiod during callus-induction than those in continuous darkness, whereas shoot regeneration was enhanced in cultures under a 16-h photoperiod in Golden Promise (GP) and Lenins (LN). These cultivars were classified as photo-inhibition type (KN5 and K3) or photo-induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 67 publications
1
3
0
Order By: Relevance
“…However, some studies, including our previous works, found that ABA was highly accumulated in HRC, but not in NRC [5]. Furthermore, the expression profiles of ABA biosynthesis genes were also upregulated, which match with our results [48].…”
Section: Roles Of Aba On Regenerable Callus Inductionsupporting
confidence: 91%
“…However, some studies, including our previous works, found that ABA was highly accumulated in HRC, but not in NRC [5]. Furthermore, the expression profiles of ABA biosynthesis genes were also upregulated, which match with our results [48].…”
Section: Roles Of Aba On Regenerable Callus Inductionsupporting
confidence: 91%
“…GA regulates plant growth by influencing stem growth and inducing germination [56], and the receptor protein GID1, DELLA protein, and PIF are involved in the signal transduction pathway of GA. In the tissue culture of immature barley embryo, the accumulation of ABA inhibited the shoot regeneration of the callus derived from immature barley embryos [57]. The downregulated DEGs related to the transduction of GA and ABA in our study might play a role in the regeneration of EC derived from immature maize embryos.…”
Section: Discussionmentioning
confidence: 60%
“…However, they found that JA was involved in the ozone response instead of IAA. Moreover, their working hypothesis was that differences in the contents of auxin and cytokinins in the calli of barley explain the difference in regeneration efficiency among cultivars in the course of experiments reported by Hisano et al (2016) and Rikiishi et al (2015). However, these two independent studies demonstrated that regeneration capacity could be explained by differences in ABA content.…”
Section: Simultaneous Analysis Of Multiple Phytohormonesmentioning
confidence: 99%